An Evaluation of The Adsorption Kinetics of Cd (Ii) Ions from Synthetic Solution Using Powdered Groundnut Shell as An Adsorbent - Ibrahim Jimoh; Abdullahi Jimoh (Genius Journals, 2021)
The adsorption of Cd (II) from synthetic solution on powdered groundnut shell was investigated under laboratory conditions to assess its ability to remove the heavy metal. This synthetic route involved the grinding and sieving of the groundnut shell with a mesh size of 2.00mm, after washing and drying. The solid was employed as an adsorbent, in which the five kinetics model were tested. The results showed that the adsorption kinetics was best described by pseudo second order kinetic models with a linear regression coefficient R2 = 1 and a rate content of 0.9950(mg/L) min-1
Keywords: Adsorption kinetics; Cd (II); powdered groundnut shell